Radiation of a charged particle in the ideally conducting metal waveguide filled with a spatially periodic layered dielectric - Tkachenko, V.I.; Tkachenko, I.V.; Tolstoluzhsky, A.P.; Khizhnyak, S.N. (Вопросы атомной науки и техники, 2018)
The parametric Cherenkov radiation of a uniformly moving particle in an ideally conducting metal waveguide filled with a spatially periodic layered dielectric is investigated analytically and numerically for the case of wavelengths comparable with the inhomogeneity period. Fields and spectra of parametric Cherenkov radiation are described. The particle's average energy losses on the period of the structure and energy fluxes of the fields are determined